Mobile Application User Experience Checklist: A Tool to Assess Attention to Core UX Principles. Issue 13 (9th August 2021) - Richardson, Brianna; Campbell-Yeo, Marsha; Smit, Michael
ABSTRACT: A user experience checklist is not a substitute for an informed expert assessment or for user studies. But what does one do when there are too many apps and not enough experts? A guideline for novice assessors can aid in assessing large numbers of apps quickly, but there are few tools assessing the quality of user experience in information-presenting mobile applications (apps). The Mobile Application User Experience Checklist (MAUX-C) is an evidence-informed, user-friendly tool that measures the overall UX quality of apps. This paper describes the development and series of preliminary validation of MAUX-C. While first developed to be used as a standardized evaluation measure when conducting systematic reviews of information-presenting mobile apps, it could also be used as a reference during app development. This paper emphasizes that in addition to high-quality information, information-presenting apps need to provide a high-quality user experience to be taken seriously in the post-truth era.